Petrochemical catalyst materials, processes, and emerging technologies - Al-Megren, Hamid, 1962-; Xiao, Tiancun, 1965- (Engineering Science Reference, 2016)
"This book addresses the latest research on emerging technological applications, catalyst materials for fuel upgrading, in addition to safety concerns and considerations within the petrochemical industry"-- Provided by publisher
Keywords: Catalytic reforming.; Catalysts.; elektronické knihy; electronic books